Sensitive high performance liquid chromatographic assay for assessment of doxorubicin pharmacokinetics in mouse plasma and tissues - Urva, Shweta R.; Shin, Beom Soo; Yang, Victor C.; Balthasar, Joseph P. (Journal of chromatography. B, Analytical technologies in the biomedical and life sciences, 2009)
A sensitive high performance liquid chromatography method (HPLC) has been developed for the quantification of doxorubicin in mouse plasma and tissues. Samples of serum or tissue homogenates, 20 μl, were analyzed following a single step protein precipitation using perchloric acid (35%, v/v). Doxorubicin was separated from the internal standard, daunorubicin, on a Zorbax 300SB C 18 column at 35 °C. Mobile phase was comprised of acetonitrile and water (25:75) containing 0.1% triethylamine, and was adjusted to pH 3 with phosphoric acid. Peaks eluting from the column were detected with a fluorescence detector with excitation and emission wavelengths of 480 and 560 nm, respectively. Standard curves were linear in the range 5–1000 ng/ml, and correlation coefficients were typically greater than 0.999. Intra-assay recoveries ranged from 94.7 to 99.9%, and inter-assay recoveries were in the range of 95.2–101%. The associated coefficient of variation (CV) was less than 10% in all cases. The method was successfully applied to investigate doxorubicin plasma pharmacokinetics and tissue distribution in athymic Fox nu mice.